Pengaruh Pertumbuhan Penjualan, Leverage dan Profitabilitas Terhadap Penghindaran Pajak dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Perusahaan IDX30 Tahun 2020–2023 - Radhika Salshabila Piscesta (PT. Hasba Edukasi Mandiri, 2025)
This study aims to find out and analyze whether sales growth, leverage, and profitability affect tax avoidance, as well as assess whether company size can moderate the relationship between the three independent variables and tax avoidance. The method used in this study is quantitative. The research population is IDX30 companies listed on the IDX in 2020-2023 which totals 47 companies. The purposive sampling technique was used in taking samples so that 64 samples were collected. The data analysis techniques used are multiple linear regression hypothesis test and Moderated Regression Analysis (MRA). The test was carried out with the SPSS (statistical product and service solutions) application device. The results of the study show that sales growth has a positive effect on tax avoidance, leverage has a negative effect on tax avoidance, and profitability has a positive effect on tax avoidance. Company size is able to strengthen the positive influence of sales growth on tax avoidance, leverage is able to weaken the negative influence on tax avoidance, and profitability is able to strengthen the positive influence on tax avoidance.